Assessment of Student Managed Investment Programs: Are they Mutual Funds or Pedagogical Devices? - Belcher, Lawrence J.; Jones, Jody (Journal of Knowledge Management Practice, 2026)
One area that has lagged behind analysis of student managed investment funds is assessment of learning. Most treatments of SMIF performance concentrate on the mutual fund aspect and look at return performance over time. Evaluating the fund in terms of common assessment metrics like learning objectives are few. Other ways are student alumni satisfaction surveys and the information transfer in the fund from experts (advisors) to novices (students). In this paper we survey existing analyses of SMIF program assessment and suggest alternative assessment tools. The objective is to discuss SMIF assessment from a pedagogical, rather than just a performance perspective.